2017
DOI: 10.1002/mdc3.12516
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic Movement Disorders in Adults and Children: A Clinical and Video Profile of 58 Indian Patients

Abstract: View Supplementary Video 1 View Supplementary Video 2 Background Psychogenic movement disorders (PMDs) represent 2% to 20% of patients with movement disorders. There is a paucity of literature on PMD in children, with most existing literature relating to adults only. Methods For this detailed report of 58 patients (33 adults and 25 children) with PMD, history was assessed in the form of disease onset, duration, precipitating factors, diagnosis, and outcome. Movement phenotype was classified in terms of its app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
5
21
0
Order By: Relevance
“…15 In another study, tremor was the most common phenomenology in adults and children with FMDs. 16 FMDs also present at the extremes of age: children and the elderly. In a meta-analysis of 120 children with FMDs reported in six different studies, 33 (27.5%) were males, [17][18][19] a figure very similar to the one reported in this study (26.3%).…”
Section: Discussionmentioning
confidence: 99%
“…15 In another study, tremor was the most common phenomenology in adults and children with FMDs. 16 FMDs also present at the extremes of age: children and the elderly. In a meta-analysis of 120 children with FMDs reported in six different studies, 33 (27.5%) were males, [17][18][19] a figure very similar to the one reported in this study (26.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Yet there are few such studies in the Indian literature that can be counted on fingers. 5,[10][11][12] . Our study showed a relatively high proportion of abnormality on imaging (35/53 or 66%) because this was done only when an abnormality was strongly suspected.…”
Section: Resultsmentioning
confidence: 99%
“…There are very few studies on spectrum, types, and etiology of childhood movement disorders from anywhere and from India and other developing countries in particular. [9][10][11][12] The spectrum and etiology of movement disorders are likely to differ in different geographic areas of the world. 13 There are no studies on pediatric movement disorders from India which have documented severity with the help of scales.…”
Section: Introductionmentioning
confidence: 99%
“…FMDs can adopt the phenomenology of any known movement disorder seen with an organic cause ( Table 1). The three most common observed phenomenology among pediatric FMDs patients included tremor, dystonia, and myoclonus (13)(14)(15). Functional gait is also not uncommon in children.…”
Section: Phenomenologymentioning
confidence: 99%